Effects of Mesenchymal Stem Cell and Growth Factor Delivery on Cartilage Repair in a Mini-Pig Model. (April 2016) - Fisher, Matthew B.; Belkin, Nicole S.; Milby, Andrew H.; Henning, Elizabeth A.; Söegaard, Nicole; Kim, Minwook; Pfeifer, Christian; Saxena, Vishal; Dodge, George R.; Burdick, Jason A.; Schaer, Thomas P.; Steinberg, David R.; et al.
Objective: We have recently shown that mesenchymal stem cells (MSCs) embedded in a hyaluronic acid (HA) hydrogel and exposed to chondrogenic factors (transforming growth factor–β3 [TGF-β3]) produce a cartilage-like tissue in vitro . The current objective was to determine if these same factors could be combined immediately prior to implantation to induce a superior healing response in vivo relative to the hydrogel alone. Design: Trochlear chondral defects were created in Yucatan mini-pigs (6 months old). Treatment groups included an HA hydrogel alone and hydrogels containing allogeneic MSCs, TGF-β3, or both. Six weeks after surgery, micro-computed tomography was used to quantitatively assess defect fill and subchondral bone remodeling. The quality of cartilage repair was assessed using the ICRS-II histological scoring system and immunohistochemistry for type II collagen. Results: Treatment with TGF-β3 led to a marked increase in positive staining for collagen type II within defects ( P < 0.05), while delivery of MSCs did not ( P > 0.05). Neither condition had an impact on other histological semiquantitative scores ( P > 0.05), and inclusion of MSCs led to significantly less defect fill ( P < 0.05). For all measurements, no synergistic interaction was found between TGF-β3 and MSC treatment when they were delivered together ( P > 0.05). Conclusions: At this early healing time point, treatment with TGF-β3 promoted the formation of collagen type II within the defect, while allogeneic MSCs had little benefit. Combination of TGF-β3 and MSCs at the time of surgery did not produce a synergistic effect. An in vitro precultured construct made of these components may be required to enhance in vivo repair in this model system.